2-Methoxy-5((3, 4, 5-trimethosyphenyl)seleninyl) phenol (SQ) inhibits cancer cell metastasis behavior of TNBC via suppressing EMT and VEGF. (25th September 2020) - Zheng, Dayong; Wu, Zhuzhu; Han, Jiaqian; Guan, Qi; Li, Zengqiang; Zuo, Daiying; Zhang, Weige; Wu, Yingliang
Abstract: Triple-negative breast cancer (TNBC) is highly metastatic and lacks effective therapeutic targets among several subtypes of breast cancer. Cancer metastasis promotes the malignancy of TNBC and is closely related to the poor prognosis of the TNBC patients. We aim to explore novel agents that effectively inhibit cancer metastasis to treat TNBC. In our study, 2-Methoxy-5((3, 4, 5-trimethosyphenyl)seleninyl) phenol (SQ), a CA-4 analogue, could inhibit cell motility and invasion in MDA-MB-231 cells, and the mechanism is closely associated to the inhibition of epithelial-to-mesenchymal transition (EMT). Meanwhile, SQ significantly inhibited the expression and secretion of vascular endothelial growth factor (VEGF) in MDA-MB-231 cells. Moreover, the conditioned medium from SQ-treated MDA-MB-231 cells significantly inhibited the motility and invasion of human umbilical vein endothelial cells (HUVECs), which was correlated with the inhibition of EMT process in HUVECs. In addition, exogenous application of VEGF reversed the occurrence of EMT in HUVECs which stimulated by conditioned medium from SQ-treated cells. Furthermore, SQ inhibited vasculogenic mimicry (VM) formation in MDA-MB-231 cells, which was associated with VE-cadherin and EphA2 down-regulation. This study indicates that SQ inhibits MDA-MB-231 cell metastasis through suppressing EMT and VEGF, thereby implicating this compound might be a potential therapeutic agent against metastatic TNBC. Highlights: SQ, a CA-4 analogue, inhibits triple-negative breast cancer cell metastasis. SQ suppresses EMT process and MMP-9 expression. SQ decreases VEGF expression and secretion. SQ inhibits endothelial cell metastasis by down-regulating VEGF secretion. SQ attenuates vasculogenic mimicry formation.